Assets and barriers of academic achievement among UP Manila dental students - Capeding, Leo J.; Jimena, Ma. Edna M.
In the University of the Philippines Manila, academic achievement of students is keenly looked into by advisers, counsellors, and administration. The university provides academic and psychosocial programs for students while they are in the university. However, despite the various support services and programs, academic achievement of U.P. students continuously needs great attention. Records show that academic delinquency among students is a growing problem for all units in the university. This is reflected in the increasing number of students who were affected by the Maximum Residency Rule (MRR). In the College of Dentistry, it is becoming common for dental students not to finish on time, adding to lots of problmes such as logistics and facilities. Academic achievement or underachievement as the case maybe, is surely an issue that the university has to deal with effectively.
Keywords: Academic achievements; Support services; Maximum Residence Rule (MRR).